Revascularization of human ovarian cortical grafts is not equally efficient from both sides of the cortex tissue - Cheng, Jiaojiao; Ruan, Xiangyan; Du, Juan; Jin, Fengyu; Gu, Muqing; Jin, Jing; Li, Yanglu; Li, Yanqiu; Wang, Zecheng; Jiang, Lingling; Zhang, Mingzhen; Liu, Anming; et al. (Frontiers in Endocrinology, 2025)
Research questionDoes early-phase revascularization of human ovarian cortical grafts exhibit spatial asymmetry between medullary and cortical surfaces in a xenotransplantation model?DesignCryopreserved ovarian tissue from five patients was transplanted bilaterally beneath the renal capsule of immunodeficient nude mice (medullary surface oriented downward). 10 ovariectomized mice (OVX) without transplantation served as controls. Grafts and blood were collected on post-transplantation days 3 and 7 (n=5 mice/point). Blood samples were also collected from OVX mice at the same time points (n=5 mice/point) for evaluation of estradiol (E2) and follicle-stimulating hormone (FSH). Vascular density (CD31+/CD34+), cellular proliferation (Ki67+), and apoptosis (TUNEL+) were quantified via immunohistochemistry at graft interfaces.ResultsCD31+ density was significantly higher at the medullary interface compared to the cortical interface at day 3 (217.25 ± 17.65 vs. 79.15 ± 14.10; P < 0.001) and day 7 (279.63 ± 22.65 vs. 197.32 ± 16.08; P = 0.002). CD34+ density showed similar medullary predominance at day 3 (149.32 ± 12.98 vs. 72.01 ± 15.48; P = 0.001) and day 7 (300.57 ± 24.65 vs. 238.35 ± 22.44; P = 0.010). Medullary vascularity increased significantly from day 3 to 7 (CD31+: P = 0.014; CD34+: P < 0.001). Cortical vascular density demonstrated significant time-dependent augmentation (P < 0.001 for both markers). Ki67+ cell percentages showed no significant differences between surfaces at day 3 (medullary vs. cortical 55.78% ± 5.05% vs. 56.48% ± 4.61%; P = 0.924) or day 7 (53.76% ± 4.65% vs. 61.80% ± 5.35%; P = 0.246). Apoptosis was significantly lower at the medullary interface than cortical interface at day 3 (4.19% ± 0.86% vs. 18.83% ± 4.05%, P = 0.001) and day 7 (0.40% ± 0.09% vs. 3.98% ± 1.10%, P = 0.000), and decreased markedly over time at both sites. Ovarian tissue transplantation significantly elevated E2 levels and suppressed FSH levels compared to the OVX controls.ConclusionsHuman ovarian grafts demonstrated superior revascularization and significantly reduced apoptosis at the medullary interface compared to the cortical surface. The restoration of hormone levels confirmed functional graft survival, validating the experimental model. These findings underscore the significance of surgical orientation in facilitating graft revascularization and mitigating cellular stress during early ovarian tissue transplantation.